(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Depression is one of the most common psychiatric disorders affecting nearly 17% of the world population and the existing antidepressant drugs used in clinical settings are largely associated with serious side effects. Tamarindus indica (Fabaceae) is a plant that has been used ethno-medicinally as a remedy for depression. Objectives: The objective of this study was to determine the antidepressant activity of methanol stem bark extract of Tamarindus indica using mice, also to determine the LD50 and phytoconstituents of same extract. Methods: Fresh leaves of Tamarindus indica were collected, pulverised and extracted using 70% v/v methanol. Phyto-constituents of the extract were screened and Median lethal dose (LD50) was determined using standard protocols. Antidepressant effects of the extract were investigated using Tail suspension test (TST) and forced swimming test (FST) models. Results: The results of median lethal dose revealed the LD50 value of 470 mg/kg body weight and the phytochemical screening showed the presence of saponins, alkaloids and glycosides. The extract at the doses of 75 and 150 mg/kg body weight significantly (p<0.05) and dose-dependently decreased the immobility time in tail suspension test (TST) as compared to control. In forced swim test, the extract significantly (p<0.05) decreased the immobility time only at the highest tested dose (150 mg/kg) when compared to placebo group. Conclusion: Methanol stem bark extract of Tamarindus indica contains secondary metabolites that possess antidepressant action and thus, justifying the traditional use of this plant in the treatment of mental disorders including depression.